CA125 but not NT-proBNP predicts the presence of a congestive intrarenal venous flow in patients with acute heart failure. Issue 5 (8th April 2021) - Núñez-Marín, Gonzalo; de la Espriella, Rafael; Santas, Enrique; Lorenzo, Miguel; Miñana, Gema; Núñez, Eduardo; Bodí, Vicent; González, Miguel; Górriz, José Luis; Bonanad, Clara; Sanchis, Juan; Bayés-Genís, Antoni; et al.
Abstract: Background: Intrarenal venous flow (IRVF) measured by Doppler ultrasound has gained interest as a potential surrogate marker of renal congestion and adverse outcomes in heart failure. In this work, we aimed to determine if antigen carbohydrate 125 (CA125) and plasma amino-terminal pro-B-type natriuretic peptide (NT-proBNP) are associated with congestive IRVF patterns (i.e., biphasic and monophasic) in acute heart failure (AHF). Methods and results: We prospectively enrolled a consecutive cohort of 70 patients hospitalized for AHF. Renal Doppler ultrasound was assessed within the first 24-h of hospital admission. The mean age of the sample was 73.5 ± 12.3 years; 47.1% were female, and 42.9% exhibited heart failure with preserved ejection fraction. The median (interquartile range) for NT-proBNP and CA125 were 6149 (3604–12 330) pg/mL and 64 (37–122) U/mL, respectively. The diagnostic performance of both exposures for identifying congestive IRVF patterns was tested using the receiving operating curve (ROC). The cut-off for CA125 of 63.5 U/mL showed a sensibility and specificity of 67% and 74% and an area under the ROC curve of 0.71. After multivariate adjustment, CA125 remained non-linearly and positively associated with congestive IRVF ( P -value = 0.008) and emerged as the most important covariate explaining the variability of the model ( R 2 : 47.5%). Under the same multivariate setting, NT-proBNP did not show to be associated with congestive IRVF patterns ( P -value = 0.847). Conclusions: CA125 and not NT-proBNP is a useful marker for identifying patients with AHF and congestive IRVF patterns.